Organic reduction in sewage by using colloid micelles: article - Badrul Hisham, Muhammad Nuril Anwar; Ku Hamid, Ku Halim (2017)
The organic matter is one of the materials that play an important role in the environment. The content of the organic matter may influence the capacity of water holding, ability of the soil and nutrient retention, in providing the sufficient nutrients for the growth of the plant. However, many research show that the organic matter is the major pollutant in wastewater. To reduce the organic matter in the wastewater, the colloid micelles, AD NANO, is used as the disinfectant. 7 methods are carried out in this research to determine the capability of AD NANO in reducing the organic matter in the wastewater. Other than that, the efficiency of AD NANO used based on four factors which are solution strength, time, temperature, and mechanical issues are determined. Based on the result, the GC-MS measurement show the total organic matter in the sample while FTIR measurement show the functional group that exist in the sample, which can react with the organic matter. As for the COD test, color test, TSS test, DO test, and turbidity test, the result show the decreased reading for the sample that had been poured with AD NANO. In the nutshell, AD NANO is proved to be one of the disinfectants that is capable of reducing the organic matter in the wastewater. In addition, the efficiency of this kind of treatment is determined by time and solution strength of AD NANO used, and the temperature of the sample is not affected by the use of AD NANO.